Avaliação da política de acesso e fomento à cultura em Fortaleza-CE: o caso do sobrado dr. José Lourenço - Borges, Jefferson José Rodrigues (2023)
The present work aims to evaluate how the notices, as management instruments implemented by Sobrado Dr. José Lourenço, act in promoting training, promotion and dissemination of cultural goods and services in the city of Fortaleza-CE. In-depth evaluation allows the research to be methodologically structured based on a qualitative approach, based on bibliographic and documentary research, associated with immersion in the field and participant observation, in addition to the application of open and semi-open interviews. As an evaluative approach, it is anchored in the assumptions of In-Depth Evaluation (Rodrigues, 2008; 2016), enabling a dense, multidimensional and interdisciplinary look in the construction of the evaluation on the context and content of cultural policy and its accessibility. It is concluded that the notices, despite culminating in instruments that enable the execution of programming in a broader and more democratic way, effectively do not produce continued effects in guaranteeing access, promotion and dissemination of goods and services in the cultural field, as they present processes that demarcate discontinuities. And, it should also be noted that these instruments, in isolation, do not guarantee the full functioning of the equipment, understanding as a challenge the guarantee of periodic maintenance of the physical space and its technologies, in addition to the implementation of a team of collaborators in the search for guaranteeing implementation of equipment actions.